The Effect of Activators againts the Ability of Active Charcoal from Nila Fish (Oreochromis niloticus) to Adsorp Cd(II) and Pb(II) Ions - Santi, M. T.; Banihabib, I.; Isnaningrum, M.; Miranda, I. B. (Indonesian Journal of Chemistry and Environment, 2019)
The purpose of this research is to how to make the active charcoal of Nila fishbone and to know effect of the variety activators against the ability of charcoal from nila fishbone waste in absorbing Cd(II) and Pb(II) ions. This research included in the experimental research. Active charcoal making process through 5 stages, namely: sampling, sample processing, the process of carbonation, the activator, and the process of neutralization. Sampling (Nila fishbone) in the restaurant, sample processing in the form of a fishbone drying in the sunshine, the process of carbonation by injecting bone for the furnace and sifted using a mess. The process of with activator HNO3 and HCl, also neutralization by making active charcoal to a neutral pH. Then, specify a contact time of 30, 60, and 90 minutes. The filtrate is further tested by Atomic Absorption Spectrophotometer (AAS) tool to know the adsorption of lead and cadmium ions. The results showed effect of HCl activator on Cd2+ and Pb2+ ions is more effective than HNO3 activator.